2014
DOI: 10.4161/auto.29592
|View full text |Cite
|
Sign up to set email alerts
|

MIR125B1represses the degradation of the PML-RARA oncoprotein by an autophagy-lysosomal pathway in acute promyelocytic leukemia

Abstract: Acute promyelocytic leukemia (APL) is characterized by the t(15;17)-associated PML-RARA fusion gene. We have previously found that MIR125B1 is highly expressed in patients with APL and may be associated with disease pathogenesis; however, the mechanism by which MIR125B1 exerts its oncogenic potential has not been fully elucidated. Here, we demonstrated that MIR125B1 abundance correlates with the PML-RARA status. MIR125B1 overexpression enhanced PML-RARA expression and inhibited the ATRA-induced degradation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…Previously reported data suggest that proteasome inhibition can induce the autophagy pathway for the degradation of ubiquitinated proteins 23, 40, 41 and that PML-RARA can be degraded by the autophagy pathway during differentiation of NB4 cells treated with ATRA or ATO. 24, 42, 43 Our data demonstrate that degradation of PML-RARA oncoprotein on combining bortezomib and ATO was mediated by autophagy that was additively induced with this combination. Reported data suggest that cargo-binding proteins such as P62, ALFY and NBR1 are involved in degrading ubiquitinated proteins.…”
Section: Discussionmentioning
confidence: 67%
“…Previously reported data suggest that proteasome inhibition can induce the autophagy pathway for the degradation of ubiquitinated proteins 23, 40, 41 and that PML-RARA can be degraded by the autophagy pathway during differentiation of NB4 cells treated with ATRA or ATO. 24, 42, 43 Our data demonstrate that degradation of PML-RARA oncoprotein on combining bortezomib and ATO was mediated by autophagy that was additively induced with this combination. Reported data suggest that cargo-binding proteins such as P62, ALFY and NBR1 are involved in degrading ubiquitinated proteins.…”
Section: Discussionmentioning
confidence: 67%
“…Notably, previous studies have indicated the crucial role of autophagy in fusion oncoprotein degradation. 20 Collectively, these data suggest that autophagy may be involved in realgar NP therapy-induced degradation of Bcr-Abl fusion oncoprotein.…”
Section: Apoptosis Is Activated By Realgar Npsmentioning
confidence: 94%
“…17 It is worth noting that autophagy participates in the therapy-induced degradation of PML-RARA oncoprotein. [18][19][20] Caveolin-1 (Cav-1), a 22-24 kDa integral membrane protein, is a principal structural component of caveolae membranes. It participates in a variety of cellular physiological and pathological processes by regulating signaling pathways.…”
mentioning
confidence: 99%
“…Transcriptional profiling has proven to be useful for determining general patterns of differential gene expression among samples [12]. Recent reports have shown that RNA-Seq is highly sensitive and can quantitatively measure gene expression in a large dynamic range of gene abundance [5,[13][14][15].…”
mentioning
confidence: 99%
“…Retinoic acid (RA) treatment for acute promyelocytic leukemia has been considered a clinical success for differentiation therapy. Although several transcription factors have been identified to play important roles in leukemogenesis [3,4], the aberrant expression of oncogenes and disruption of tumor suppressor genes are most likely involved in processes responsible for blocking leukemia cell differentiation [5][6][7][8][9][10][11].…”
mentioning
confidence: 99%